OCEANS 2011 IEEE - Spain 2011
DOI: 10.1109/oceans-spain.2011.6003627
|View full text |Cite
|
Sign up to set email alerts
|

Study of pilot designs for cyclic-prefix OFDM on time-varying and sparse underwater acoustic channels

Abstract: Abstract-Estimation of time-varying and sparse channels is a topic that has attracted considerable interest lately, especially for underwater acoustic communication. In the context of multicarrier transmission, several important questions remain unanswered: i) should pilots be placed in clusters as for timevarying, non-sparse channels, or randomly dispersed between the data as common in the Compressive Sensing literature; ii) as pilot and data subcarriers cannot be perfectly separated at the receiver due to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…At the same time compressed sensing algorithms uniformly outperformed the LS and subspace methods and could handle channels with significant Doppler spread. In [58] the same authors discussed sparse channel estimation for time-varying UWA channels using MC transmission. In case when pilots and data symbols were not separated at the receiver, it was shown that subcarriers corresponding to data symbols could be used to observe the ICI caused by the neighbouring pilot subcarriers.…”
Section: Channel Estimation and Equalization Techniques For Multimentioning
confidence: 99%
“…At the same time compressed sensing algorithms uniformly outperformed the LS and subspace methods and could handle channels with significant Doppler spread. In [58] the same authors discussed sparse channel estimation for time-varying UWA channels using MC transmission. In case when pilots and data symbols were not separated at the receiver, it was shown that subcarriers corresponding to data symbols could be used to observe the ICI caused by the neighbouring pilot subcarriers.…”
Section: Channel Estimation and Equalization Techniques For Multimentioning
confidence: 99%
“…Transmission The challenges in pilot design for multicarrier transmission over underwater acoustic time-varying channels are two-fold [40,41]: 1) Sets of adjacent observations are needed to estimate the inter-carrier interference (ICI) coefficients; 2) Keeping pilot and data symbols orthogonal at the receiver is challenging due to the ICI. Generally there are three types of pilot insertion methods for OFDM system, comb-type; block-type; hexagonal gridtype, etc.…”
Section: Pilot Signal Design For Ofdm Multicarriermentioning
confidence: 99%
“…For underwater acoustic (UWA) channel estimation, a clustered pilot design has been proposed [12]. A random pilot allocation algorithm based on UWA channel is proposed to look for the optimized pilot arrangements at the transmitter, which requires a large amount of memory [13].…”
Section: Introductionmentioning
confidence: 99%